The cyanobacterial FtsH4 protease controls accumulation of protein factors involved in the biogenesis of photosystem I - Koník, Peter; Skotnicová, Petra; Gupta, Sadanand; Tichý, Martin; Sharma, Surbhi; Komenda, Josef; Sobotka, Roman; Krynická, Vendula (Biochimica et biophysica acta. Bioenergetics, 2024)
Membrane-bound FtsH proteases are universally present in prokaryotes and in mitochondria and chloroplasts of eukaryotic cells. These metalloproteases are often critical for viability and play both protease and chaperone roles to maintain cellular homeostasis. In contrast to most bacteria bearing a single ftsH gene, cyanobacteria typically possess four FtsH proteases (FtsH1-4) forming heteromeric (FtsH1/3 and FtsH2/3) and homomeric (FtsH4) complexes. The functions and substrate repertoire of each complex are however poorly understood. To identify substrates of the FtsH4 protease complex we established a trapping assay in the cyanobacterium Synechocystis PCC 6803 utilizing a proteolytically inactivated trapFtsH4-His. Around 40 proteins were specifically enriched in trapFtsH4 pulldown when compared with the active FtsH4. As the list of putative FtsH4 substrates contained Ycf4 and Ycf37 assembly factors of Photosystem I (PSI), its core PsaB subunit and the IsiA chlorophyll-binding protein that associates with PSI during iron stress, we focused on these PSI-related proteins. Therefore, we analysed their degradation by FtsH4 in vivo in Synechocystis mutants and in vitro using purified substrates. The data confirmed that FtsH4 degrades Ycf4, Ycf37, IsiA, and also the individual PsaA and PsaB subunits in the unassembled state but not when assembled within the PSI complexes. A possible role of FtsH4 in the PSI life-cycle is discussed.
Keywords: Photosystem II Protein Complex; metaloproteasy; fotosystém I (proteinový komplex); Synechocystis; Peptide Hydrolases; FtsH4 protease; Metalloproteases; Photosystem I; Photosystem I Protein Complex; proteasy; Thylakoid membrane; Assembly factors; fotosystém II (proteinový komplex)